Sebuah Teori Lama Mengenai Interpretasi Teks yang Tampak Baru - ., Purwito (CORAK, 2012)
Hermeneutics as an object of study is a means of understanding the âactualâ as old as human beings age on this earth. Hermeneutics is very important in the process of human interaction, so the study was conducted to study the hermeneutics in his position as a science of interpretation that can be studied in ontological, epistemological, and axiological. As a science, hermeneutics emerged as a dominant movement in European Protestant theology which states that hermeneutics is a focal point of the current theological issues. Associated with his position as a science, the study was conducted to determine hermeneutics in the concept of etymology and terminology, knowing on historically with the figures who pioneered the science of it, his position as a theory of interpretation multidisciplinary, as well as the position and function as a historiographical approach through philological approach. Keywords: hermeneutics, the theory of interpretation, and text.